2023
DOI: 10.3350/cmh.2022.0422
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hepatitis B with concurrent metabolic dysfunction-associated fatty liver disease: Challenges and perspectives

Abstract: The prevalence of metabolic dysfunction-associated fatty liver disease (MAFLD) has increased among the general population and chronic hepatitis B (CHB) patients worldwide. Although fatty liver disease is a well-known risk factor for adverse liver outcomes like cirrhosis and hepatocellular carcinoma (HCC), its interactions with the hepatitis B virus (HBV) and clinical impacts seem complex.The presence of hepatic steatosis may suppress HBV viral activity, potentially leading to attenuated liver injury. In con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 72 publications
0
32
0
1
Order By: Relevance
“…In patients with combined CHB and fatty liver, there are controversial results, with a few reports suggesting that fatty liver was associated with a higher probability of HCC, 20,21 and others reporting the contrary, that fatty liver was associated with a lower risk of HCC. 6,[22][23][24] These discordant results may be attributed to the complex relationships between hepatic steatosis and hepatitis B virus (HBV) infection, such as the direct suppression of HBV viral activity by steatosis, 25 which may have affected the outcome, and the inclusion of heterogeneous CHB patients with or without antiviral therapy or different adherence to antiviral drugs. However, in an analysis of only fully virologically suppressed patients but with advanced chronic liver disease (≥10 kPa), a lower degree of liver fat content was shown to be significantly associated with a higher risk of HCC, which corresponds to the results shown in our study.…”
Section: In Context With Current Literaturementioning
confidence: 99%
“…In patients with combined CHB and fatty liver, there are controversial results, with a few reports suggesting that fatty liver was associated with a higher probability of HCC, 20,21 and others reporting the contrary, that fatty liver was associated with a lower risk of HCC. 6,[22][23][24] These discordant results may be attributed to the complex relationships between hepatic steatosis and hepatitis B virus (HBV) infection, such as the direct suppression of HBV viral activity by steatosis, 25 which may have affected the outcome, and the inclusion of heterogeneous CHB patients with or without antiviral therapy or different adherence to antiviral drugs. However, in an analysis of only fully virologically suppressed patients but with advanced chronic liver disease (≥10 kPa), a lower degree of liver fat content was shown to be significantly associated with a higher risk of HCC, which corresponds to the results shown in our study.…”
Section: In Context With Current Literaturementioning
confidence: 99%
“…Thorough investigations are essential to validate and clarify the optimal therapeutic choice in this specific patient population. 19,40,41 Furthermore, a multidisciplinary approach, involving physicians from diverse specialties and dietitians, should be adopted in the patient care plan to optimize glycemic control and mitigate adverse outcomes.…”
Section: Essential Criterionmentioning
confidence: 99%
“…Given the increasing prevalence of fatty liver and metabolic syndrome in chronic viral hepatitis patients, the impact of concurrent MAFLD in chronic viral hepatitis is a growing concern. 7 Recent studies demonstrated that MAFLD in chronic viral hepatitis patients was associated with increased risk of poor clinical outcome 8 and significant liver fibrosis. 9 However, no study has yet investigated whether chronic viral hepatitis patients at high risk of a poor long-term outcome can be identified based on MAFLD subgroup.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic viral hepatitis can coexist with MAFLD. Given the increasing prevalence of fatty liver and metabolic syndrome in chronic viral hepatitis patients, the impact of concurrent MAFLD in chronic viral hepatitis is a growing concern 7 . Recent studies demonstrated that MAFLD in chronic viral hepatitis patients was associated with increased risk of poor clinical outcome 8 and significant liver fibrosis 9 .…”
Section: Introductionmentioning
confidence: 99%